FLOATING GASTRORETENTIVE OF AMOXICILLIN USING HARD ALGINATE CAPSULES AND ITS ANTIBACTERIAL ACTIVITIES - Arianto, Anayanti; Bangun, Hakim; Yohana, Ade; Silalahi, Jansen (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to formulate floating gastroretentive of amoxicillin using hard alginate capsules shell and to evaluate antibacterial activities of floating gastroretentive of amoxicillin. Methods: Alginate capsules shell were made by using sodium alginate 80-120 cP. Amoxicillin was prepared in solid dispersion to obtain sustained release requirement for 12 hours. Solid dispersion was prepared by solvent method using polyvinylpyrrolidone (PVP) K30. The solid dispersion was characterized by X-ray diffraction and FTIR analysis. The drug release test was carried out by using USP paddle method in simulated gastric fluid. Concentrations of amoxicillin were determined by using spectrophotometer UV at 272 nm. The antibacterial activity of aliquots dissolution were assessed by using agar plate diffusion method against Staphylococcus aureus and Escherichia coli as bacterial model. Results: The alginate capsules shell were made from sodium alginate 80-120 cP with size 0. The dissolution test results showed that amoxicillin in the form of solid dispersions with weight ratio amoxicillin with PVP K30 was 1:1 provided sustained release of amoxicillin during 12 hours, while the release of amoxicillin without solid dispersion was too slow. The floating lag time was 0 minute and floating time was more than 12 hours. The X-ray diffraction pattern of amoxicillin solid dispersion had amorphous shape. Antibacterial activity test showed that the dissolution aliquots of amoxicillin solid dispersion were effective against Staphylococcus aureus and Escherichia coli. Conclusions: Based on the results of this study, it is concluded that the alginate capsules shell can be used for preparation of floating gastroretentive of amoxicillin using amoxicillin solid dispersion and the dissolution aliqouts give antibacterial effect.